Solubility Prediction of Pyrene in Non-Aqueous Solvent Mixtures Using Jouyban-Acree Model - JOUYBAN, ABOLGHASEM; KHOUBNASABJAFARI, MARYAM; E. ACREE JR, WILLIAM (Asian Journal of Chemistry, 2010)
Applicability of a previsouly presented quanitative structure property relationship was extended to predict the solubility of pyrene in binary solvent mixtures at 26°C using solubility parameter, boiling point, vapour pressure and density of solvents as independent variables employing 63 solubility data sets. The mean percentage deviation of experimental and predicted solubilities was computed as a measure of accuracy where the mean percentage deviations were ca. 6 and ca. 10 %, respectively for pyrene solubillity data in binary and ternary solvents for the best prediction method.